A Comparative Numerical Study of Meshing Functionals for Variational Mesh Adaptation (Journal of Mathematical Study, 2015)
We present a comparative numerical study for three functionals used forvariational mesh adaptation. One of them is a generalization of Winslow's variable diffusionfunctional while the others are based on equidistribution and alignment. Thesefunctionals are known to have nice theoretical properties and work well for most meshadaptation problems either as a stand-alone variational method or combined withinthe moving mesh framework. Their performance is investigated numerically in termsof equidistribution and alignment mesh quality measures. Numerical results in 2Dand 3D are presented.
Keywords: Variational mesh adaptation; Mesh adaptation; Moving mesh; Equidistribution; Alignment; Mesh quality measures.